Cords of affection : constructing constitutional union in early American history - Pears, Emily (American political thought., 2021)
"American democracy seems to be running on empty. Beyond our falling faith in institutions, Americans seem to have lost trust in one another and faith in our common political enterprise. Polarization, culture wars, and protest movements have called into question our personal commitments to the constitutional community and the content of that union. Political commentators offer a huge array of descriptions of the actual problem-from polarization to anti-establishment cultural movements, and an even broader array of proposed solutions ranging from the impractical to the apocalyptic. While some of these proposals are promising, few are adequately grounded in the deep history of American politics and American political thought in particular. Emily Pears argues that a part of what we are facing today is a weakening of political attachments. Defined as the deep-seated and instinctual emotional connections between individuals and their constitutional union, attachments have long been the foundation on which our voluntary, republican society is based. But attachments are not formed automatically and require tending to maintain their strength. Pears looks back to the American Founding, a time when attachments were particularly weak, to understand how such attachments might be constructed and nurtured today. Cords of Affection explores three main mechanisms for developing and sustaining political attachments: the utilitarian use of material self-interest, the use of historical narrative to create a shared cultural identity, and the participatory use of political parties and direct democracy. While no strategy has proved successful in itself, the history of attachment-building provides lessons and resources for reforging a unified American political community today"--